2020
DOI: 10.3390/ijerph17207545
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Government Support on Performing Artists’ Job and Life Satisfaction: Findings from The National Survey in Korea

Abstract: In this study, we aim to propose motives that can help increase the creative activities of Korean performing artists and discuss the policy implications for the sustainable management of Korean performing arts. First, we investigate the characteristics of Korean artists that receive subsidies as a form of government support for undertaking artistic activities. Second, we examine whether receipt of such grants influences the artists’ job and life satisfaction. Through a logistics model, we reconstructed the “20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It demonstrated that art might be considered an excellent public benefit and a shared asset in society. The study concluded that artist subsidies should be increased to improve artists' quality of life and the long-term viability of artistic endeavours (Park & Kim, 2020). Many young artists abandon their careers because they cannot balance creating work, living, and earning money.…”
Section: Resultsmentioning
confidence: 99%
“…It demonstrated that art might be considered an excellent public benefit and a shared asset in society. The study concluded that artist subsidies should be increased to improve artists' quality of life and the long-term viability of artistic endeavours (Park & Kim, 2020). Many young artists abandon their careers because they cannot balance creating work, living, and earning money.…”
Section: Resultsmentioning
confidence: 99%